RETURN ON ASSETS: DEBT TO ASSET RATIO AND CURRENT RATIO IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ihsan Rambe; Bahril Datuk (CERED Indonesia Institute, 2021)
This study aims to determine whether the Current Ratio and Debt To Asset Ratio have an effect either partially or simultaneously on Return On Assets in Food and Beverage companies listed on the Indonesia Stock Exchange. The approach used in this study is an associative approach. The population used in this study were 26 companies and a sample that met the criteria (purposive sampling) was 7 companies. The data collection technique used in this study uses documentation techniques and the data sources used in this study are secondary data sources published by companies on the official website of the Indonesia Stock Exchange.www.idx.co.id. The data analysis technique used in this study is a quantitative technique with multiple linear regression analysis, hypothesis testing and coefficient of determination test. The results of this study are partially Current Ratio has no significant effect on Return On Assets. Partially the Debt To Asset Ratio has a significant effect on Return On Assets. Simultaneously Current Ratio and Debt To Asset Ratio have a significant effect on Return On Assets in Food and Beverage companies listed on the Indonesia Stock Exchange for the 2014-2019 period.